Lightyears behind : potential solutions for the interpretative ambiguities left by Article VI of the Outer Space Treaty - Hobe, Stephan (University of Pretoria, 2023)
Mini Dissertation (LLM (International Air, Space and Telecommunications Law))--University of Pretoria, 2023.